Putting PIRLS to Use in Classrooms Across the Globe Evidence-Based Contributions for Teaching Reading Comprehension in a Multilingual Context - Bruggink, Marian (IEA Research for Educators, 2022)
This open access book provides teachers with approaches to strengthen reading comprehension instruction based on scientific research and evidence-based didactic principles. In this volume, the Progress in International Reading Study (PIRLS) framework is used to inform teachers about the skills and knowledge that students need to comprehend certain texts. The book gives practical guidance on how a teacher can help students to learn these skills, specifically, when teaching reading to multilingual students. Good practices from schools in five participating PIRLS countries-Chile, Chinese Taipei, England, Georgia, and Spain-are shared. A description of the schools' education in reading comprehension is provided with practical tips and example lessons. These insights into daily reading education in multilingual classrooms across the globe can be an inspiration to teachers all over the world.